Monotheism and existentialism - Casewell, Deborah (Cambridge elements. Elements in religion and monotheism, 2022)
Existentialism is often seen and at times parodied as the philosophy of individuality, authenticity, despair, and defiance in a godless world. However, it cannot be understood without reference to religion, and in particular the monotheism of Christianity. Even the existentialist slogan, 'existence precedes essence', is formulated in relation to monotheism. This Element will show that monotheism and existentialism are intertwined: they react to each other, and share content and concerns. This Element will set out a genealogy of existentialist thought; explore key atheistic and theistic existentialists; and argue that there are productive conversations to be had as regards key concepts such as freedom and authenticity, relationality, and ethics.